2022
DOI: 10.3389/fpubh.2022.895991
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors and Outcomes of Sepsis in Critically Ill Post-craniotomy Patients: A Single-Center Prospective Cohort Study

Abstract: BackgroundData concerning the epidemiology of sepsis in critically ill post-craniotomy patients are scarce. This study aimed to assess the incidence, risk factors, and outcomes of sepsis in this population.MethodsThis was a single-center prospective cohort study. Post-craniotomy patients admitted to the intensive care unit (ICU) were screened daily for the presence of infection and sepsis.ResultsOf the 900 included patients, 300 developed sepsis. The cumulative incidence of sepsis was 33.3% [95% confidence int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Lower GCS scores are also associated with the incidence of VAP in TBI patients [32,38], which may be related to the fact that patients with moderate and severe TBI require open surgery, and respiratory support, and are susceptible to urinary tract infection. A single-center prospective cohort study including 900 patients found that lower GCS scores and higher APACHE (Acute Physiology and Chronic Health Evaluation) II scores are independent risk factors for secondary sepsis in TBI patients after operation [39].…”
Section: Discussionmentioning
confidence: 99%
“…Lower GCS scores are also associated with the incidence of VAP in TBI patients [32,38], which may be related to the fact that patients with moderate and severe TBI require open surgery, and respiratory support, and are susceptible to urinary tract infection. A single-center prospective cohort study including 900 patients found that lower GCS scores and higher APACHE (Acute Physiology and Chronic Health Evaluation) II scores are independent risk factors for secondary sepsis in TBI patients after operation [39].…”
Section: Discussionmentioning
confidence: 99%
“…34 In a higher risk neurosurgical cohort of postcraniotomy patients (all admitted to the ICU), cumulative incidence of sepsis was 33.3% (95% CI: 30.2–36.4), and the mortality rate in those with sepsis was 13.7 versus 8.3% for those without sepsis. 53…”
Section: Sepsis In Specific Patient Populationsmentioning
confidence: 99%
“…34 In a higher risk neurosurgical cohort of postcraniotomy patients (all admitted to the ICU), cumulative incidence of sepsis was 33.3% (95% CI: 30.2-36.4), and the mortality rate in those with sepsis was 13.7 versus 8.3% for those without sepsis. 53 A single-center study of patients admitted to a cardiac intensive care unit after cardiac surgery utilized physician review and Sepsis-3 definitions; the authors reported a much higher incidence of sepsis (9.5%), of whom half had proven infections (4.8%) and half had suspected infection alone (4.7%). The adjusted odds ratio for 30-day mortality for patients with sepsis versus without was 6.6 (95% CI: 2.6-1.7) for confirmed infection and 3.7 (95% CI: 1.1-10.2) for suspected infection.…”
Section: Sepsis In Surgical and Postprocedural Patientsmentioning
confidence: 99%